Environmental Mapping of Paracoccidioides spp. in Brazil Reveals New Clues into Genetic Diversity, Biogeography and Wild Host Association. - Thales Domingos Arantes; Raquel Cordeiro Theodoro; Marcus de Melo Teixeira; Sandra de Moraes Gimenes Bosco; Eduardo Bagagli (Public Library of Science (PLoS), 2016)
BACKGROUND:Paracoccidioides brasiliensis and Paracoccidioides lutzii are the etiological agents of Paracoccidioidomycosis (PCM), and are easily isolated from human patients. However, due to human migration and a long latency period, clinical isolates do not reflect the spatial distribution of these pathogens. Molecular detection of P. brasiliensis and P. lutzii from soil, as well as their isolation from wild animals such as armadillos, are important for monitoring their environmental and geographical distribution. This study aimed to detect and, for the first time, evaluate the genetic diversity of P. brasiliensis and P. lutzii for Paracoccidioidomycosis in endemic and non-endemic areas of the environment, by using Nested PCR and in situ hybridization techniques. METHODS/PRINCIPAL FINDINGS:Aerosol (n = 16) and soil (n = 34) samples from armadillo burrows, as well as armadillos (n = 7) were collected in endemic and non-endemic areas of PCM in the Southeastern, Midwestern and Northern regions of Brazil. Both P. brasiliensis and P. lutzii were detected in soil (67.5%) and aerosols (81%) by PCR of Internal Transcribed Spacer (ITS) region (60%), and also by in situ hybridization (83%). Fungal isolation from armadillo tissues was not possible. Sequences from both species of P. brasiliensis and P. lutzii were detected in all regions. In addition, we identified genetic Paracoccidioides variants in soil and aerosol samples which have never been reported before in clinical or armadillo samples, suggesting greater genetic variability in the environment than in vertebrate hosts. CONCLUSIONS/SIGNIFICANCE:Data may reflect the actual occurrence of Paracoccidioides species in their saprobic habitat, despite their absence/non-detection in seven armadillos evaluated in regions with high prevalence of PCM infection by P. lutzii. These results may indicate a possible ecological difference between P. brasiliensis and P. lutzii concerning their wild hosts.